Tracheostomy outcomes in coronavirus disease 2019: a systematic review and meta-analysis - Sharma, Ankur; D. Goel, Akhil; Bhardwaj, Pankaj; Kothari, Nikhil; Goyal, Shilpa; Kumar, Deepak; Gupta, Manoj; K. Garg, Mahendra; K. Chauhan, Nishant; Bhatia, Pradeep; Goyal, Amit; Misra, Sanjeev (Anestezjologia Intensywna Terapia, 2021)
Tracheostomy is a standard surgical procedure that is used in critically ill patients who require sustained mechanical ventilation. In this article, we review the outcomes of coronavirus disease 2019 (COVID-19) patients who underwent tracheostomy. We searched for relevant articles on PubMed, Scopus, and Google Scholar, up to April 20, 2021. This meta- analysis examines ventilation liberation, decannulation, and hospital mortality rates in COVID-19 patients who have undergone tracheostomy. Two investigators evaluated the articles, and the differences of opinion were settled by consensus with a third author. A total of 4366 patients were included in 47 related articles for this meta-analysis. After data pooling, the proportions of ventilation liberation, decannulation and mortality were found to be 48% (95% CI: 31–64), 42% (95% CI: 17–69) and 18% (95% CI: 9–28) respectively. The Luis Furuya-Kanamori (LFK) index values for ventilation liberation, decannulation and mortality were 4.28, 1.32 and 0.69. No transmission of the disease attributable to participating in tracheostomy procedures was reported in most of the included articles.